Research Model of Supply Chain and Dynamic Capabilty on Business Performance of Madura Duck MSMEs in Bekasi - Syahyono, Syahyono; Mayvea, Nadya Artha Joecha; Haniammaria, Erina; Ardiyanti, Difa; Ramadina, Risma Ayu (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research intends to analyze how supply chain management and dynamic capability impact the business performance of Madura Duck MSMEs located in Bekasi. To explore this, a quantitative method is employed using an explanatory approach to investigate the causal links among the variables. The study involved a sample of 100 participants, specifically owners and managers of Madura Duck MSMEs in Bekasi, chosen through a purposive sampling method. Data were gathered via a questionnaire that utilized a Likert scale ranging from 1 to 10, with analysis conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The result here is proved that the supply chain positively influences business performance significantly, presenting a coefficient of 0.307 (t = 2.241, p = 0.025). Meanwhile, dynamic capability has an even greater impact on business performance, with a coefficient of 0.530 (t = 4.009, p = 0.000). Additionally, there is a noteworthy indirect impact by the supply chain at the business performance through dynamic capability, which has a coefficient of 0.438 (t = 3.918, p = 0.000). The research model accounts for 64.5% of the variations in the business performance of Madura Duck MSMEs in Bekasi. This study offers both theoretical and practical insights into how the supply chain and dynamic capability affect the business performance of culinary MSMEs. The results imply that fostering robust dynamic capabilities, backed by efficient supply chain management, is crucial for enhancing the business performance of Madura Duck MSMEs in Bekasi.